How to Handle the Crisis in Greece? Empirical Evidence Based on a Survey of Economics Experts - Niklas Potrafke; Markus Reischmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
We asked experts from 113 countries polled by the CESifo World Economic Survey for their opinions on how to handle the crisis in Greece. 61.9% of the experts surveyed were not in favour of Greece exiting the Eurozone in the course of the negotiations held in June and July 2015. However, experts in countries such as Germany, the United Kingdom, Sweden, the Czech Republic, Denmark, and Slovakia were in favour of Greece exiting the Eurozone. The share of experts who were in favour of Greece staying in the Eurozone increased to 69.8% in October 2015. 72.4% of experts surveyed believed that the IMF should provide credit to Greece and 83.6% stated that the IMF should engage in economic reform programmes. Econometric evidence shows that experts from those Eurozone countries with high public debt-to-GDP-ratios were less likely to support the Grexit: when the debt-to-GDP-ratio increased by one percentage point, the likelihood of survey participants favouring the Grexit decreased by around 0.35 percentage points. Support for IMF reforms, by contrast, proved far less controversial.
Keywords: H63; C83; H12; F53; E42; F45; 330; Greece; Grexit; experts' survey; public debt crisis; IMF; international organisations